Is Cognitive Training Effective for Improving Executive Functions in Preschoolers? A Systematic Review and Meta-Analysis - Scionti, Nicoletta; Cavallero, Marina; Zogmaister, Cristina; Marzocchi, Gian Marco (Frontiers in Psychology, 2020)
In the present meta-analysis, we examined the effect of cognitive training on the Executive Function (EF) of preschool children (age range: 3-6 years). We selected a final set of 32 studies from 27 papers with a total sample of 123 effect sizes. We found an overall effect of cognitive training for improving EF (g = .352; k = 123; p < .001), without significant difference between near and far transfer effects on executive domains. No significant additional outcome effects were found for behavioral- and learning-related outcomes. Cognitive training programs for preschoolers are significantly more effective for developmentally at-risk children (ADHD or low socio-economic status) than for children with typical development and without risks. Other significant moderators were computerized versus non-computerized training, individual versus group sessions, and length of training. The number of sessions was not a significant moderator. This is the first demonstration of cognitive training far transfer effects among different executive processes. We discuss this result in relationship with the lower level of modularization of EFs in younger children.